Development of a mobile powered hole digger for orchard tree cultivation using a slider-crank feed mechanism - Wangyuan, Zong; Jingliang, Wang; Xiaomao, Huang; Dong, Yu; Yingbiao, Zhao; Graham, Sean (International Journal of Agricultural and Biological Engineering, 2016)
The powered hole digger is one of the most important orchard machines. The power consumption of its drill is an important factor affecting the performance and operation of the device. The drill power consumption of the digger at a constant feed rate is directly proportional to digging depth. This research discusses a newly designed powered hole digger using a slider-crank feed mechanism. The motion characteristics of the powered hole digger feeding mechanism was analysed. Additionally, an experiment was conducted to determine the characteristics of the drill power consumption. It can be concluded that there was a positive correlation between the drill power consumption and the powered hole digger feed rate. It was observed that when digging depth reached 200 mm, the drill power consumption reached the maximum power rating; subsequently the drill power consumption decreased with an increase of digging depth. When the drill reached the bottom of the hole, the power consumption of the new powered hole digger did not exceed the maximum designed power rating, hence the drill motor would not stall. Keywords: powered hole digger, crank-slider, drill power consumption, orchard tree DOI: 10.3965/j.ijabe.20160903.1784 Citation: Zong W Y, Wang J L, Huang X M, Yu D, Zhao Y B, Graham S. Development of a mobile powered hole digger for orchard tree cultivation using a slider-crank feed mechanism. Int J Agric & Biol Eng, 2016; 9(3): 48－56.